Pertanggungjawabaan Pidana Anak di Bawah Umur Mengonsumsi Minuman Keras : Studi di Desa Ujoh Bilang Kabupaten Mahakam Ulu - Khofifah Laila Oktavia; La Syarifudin; Agustina Wati (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Minors today are increasingly involved in criminal acts, and this does not happen without reason. One contributing factor is the consumption of alcoholic beverages. Children in Ujoh Bilang Village have started consuming alcohol, influenced by several factors, despite being underage. They consume both branded alcoholic drinks and traditional beverages such as arak. Based on research conducted in Ujoh Bilang Village, Mahakam Ulu, several factors have been identified as reasons why minors consume alcohol. These include internal factors within the child, external factors such as family influence, environment, alcohol vendors, and cultural factors. These elements serve as the background for underage alcohol consumption in the village. According to the research findings, minors who consume alcohol are not subjected to criminal punishment but are instead given warnings or educational guidance and then returned to their parents. However, minors can be held criminally responsible under the juvenile criminal justice system if they are unable to control themselves due to intoxication, leading to criminal acts such as accidents, fights, or even murder. In such cases, minors may be prosecuted for their actions.